Virtual reference service in the Muslim world: opportunities and challenges - Abu Bakar, Ahmad Bakeri (University of Nebraska--Lincoln Libraries, 2009)
The reference function has undergone changes in the variety of services offered and in the service itself. One area of change is in the deployment of the technologies used to meet the demands of users. Remote access by library users is a serious challenge to reference services. They must develop strategies to cope with the demands of the user for remote access.